Using Digital Storytelling: Ideas to Boost Students Autonomous Learning - Yansyah Yansyah; Andriany Hadisyah (UMBanjarmasin, 2018)
Autonomous learning now becomes a prominent issue in English language teaching. The concept of this learning model is to make the students use most of their potential to boost the learning outcome. Digital storytelling is relatively new in education, in which we use digital tools to tell a story. This technique combines both technology and learning to make students explore their digital literacy and express their language ability. The present paper explains in detail how storytelling can be used for instructional purposes, both from literature and research perspective. Then, it will list some ideas, which can be utilized to apply this technique in English language classroom and to make students be more autonomous in learning. A Sample of lesson plan will be given to make this paper share more practical benefit for the readers. Finally, it is expected that this article can give some insights for teachers to bring joyful and innovation in their teaching practices.